Crisis and the war and climate refugees: from international protocols to journalistic narratives - Victor, Cilene (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
The contemporary humanitary crisis, with more than 65 million refugees of violent conflicts and climate chages, has put under distrust the development models and stressed the theoretical and practical fragilities for confronting them. This paper reviews the essence of the debates at the World Humanitarian Summit, analyzes the narratives of international protocols on the topic and advocates for media intervention through humanized journalistic narratives.